The role of calcium in wheat starch-Mesona chinensis polysaccharide gels: Rheological properties, in vitro digestibility and enzyme inhibitory activities. (January 2019) - Yuris, Anynda; Hardacre, Allan Keith; Goh, Kelvin Kim Tha; Matia-Merino, Lara
Abstract: The interaction between Mesona chinensis polysaccharide (MCP) and wheat starch was dependent on the presence of calcium that is naturally present in the extract of Mesona chinensis (MC). Partial removal of the calcium from MCP resulted in a 55% decrease in the final storage modulus (G') and 20% increase in digestibility of a 100 mg/g wheat starch gel containing 50 mg/g MCP. The weakening of the gel was associated with a reduction in MCP-MCP interactions, as a result of an increase in electrostatic repulsive forces upon partial calcium removal. This resulted in the formation of a less extended network comprising of amylose and fractions of uninteracting MCP. A combination of lower gel strength and formation of less amylose-MCP complexes was thought to be responsible for the increase in the digestibility of the gel. "Calcium-reduced MCP" was found to inhibit the activities of α-amylase and α-glucosidase uncompetitively. Partial reduction of calcium was likely to alter the conformation of MCP, resulting in a polysaccharide conformation that is favourable for α-amylase binding but less so for α-glucosidase binding. Highlights: Calcium affects Mesona chinensis polysaccharide (MCP) and wheat starch interaction. Reduction in the calcium level of MCP reduces the strength of wheat starch-MCP gels. Partial calcium reduction increases the digestibility of starch-MCP gels. Calcium-reduced MCP inhibits α-amylase and α-glucosidase activities.